THE EFFECT OF TASK-BASED LEARNING ON THE STUDENTS' READING ABILITY COMPREHENSION AT EIGHTH GRADE OF SMP NEGERI 8 PEMATANGSIANTAR - Ginting, Selliani Br; Sinaga, Asima Rohana; Manihuruk, Leonita Maria Efipanias (Jurnal Ilmiah Pendidikan dan Keislaman, 2025)
The purpose of reading comprehension is to get some skills in understanding the text. So, they can master English well and can comprehend the aspects of reading comprehension well. This purpose of this research is to find out the effect of using task-based learning on students' reading comprehension at the eighth grade of SMP Negeri 8 Pematangsiantar. In this study, the researcher use quasi experimental research The research sample is 31 students of class Vlll-7 as the experimental class and 31 students of class Vlll-8 as the control class The instrument of this research is a reading test that is conduct into two tests, pre-test and post-test The instrumentation is create into 25 multiple questions. Based on the data analysis by using Paired Sample T-test in SPSS 21 for windows, the mean of pre-test score in the experimental class was 59.226 while the mean of post-test score in the experimental class was 87.871 It can be conclude that the students' who are teach by using task-based learning as teaching method are better than students who are taught by using conventional method The significance of the test is 0.000 which is lower than the significance level that is 0.05 with 5% of degree Moreover, it is also find that the students' score is improving especially for the students in the experimental class which gained 28.645 of their average score. The conclusion based on the data task based learning is a good method to Increase the students reading comprehension and the suggestion is the teacher should be more creative in teaching and learning process.